Hide-seek-hide? The effects of financial secrecy on cross-border financial assets - Petr Janský; Tereza Palanská; Miroslav Palanský (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Excessive financial secrecy facilitates illicit financial flows, which constitute a major developmental challenge for low-income economies and cause significant tax revenue losses for governments around the world. In this paper we estimate the semi-elasticity of cross-border financial assets to changes in financial secrecy and how it differs for countries at various income levels. We develop a new financial secrecy dataset for the 2011-20 period, which covers many specific policies in addition to the previously studied automatic information exchange. We then combine this with data on cross-border financial assets and find that investors do indeed react to changes in financial transparency by relocating their assets to offshore financial centres, which remain, or have recently become, more financially secretive than other countries (here, secrecy jurisdictions). In agreement with our theoretical predictions, we document that this effect is highly non-linear and stronger for portfolio investment than for bank deposits. Overall, we find a much stronger relocation effect for assets originating from lower-income countries.
Keywords: F36; F65; G28; H26; 330; financial secrecy; financial transparency; secrecy jurisdictions; tax havens; offshore financial centres